The LIM Protein AJUBA is a Potential Oncogenic Target and Prognostic Marker in Human Cancer via Pan-Cancer Analysis - Song, Na; Liu, Jia; Zhang, Ke; Yang, Jie; Cui, Kai; Miao, Zhuang; Zhao, Feiyue; Meng, Hongjing; Chen, Lu; Chen, Chong; Li, Yushan; Shao, Minglong; et al. (Frontiers in Cell and Developmental Biology, 2022)
Purpose: The LIM protein AJUBA involved in multiple biological functions, and its aberrant expression is associated with the oncogenesis and progression in various types of cancer. However, there is no pan-cancer analysis of AJUBA was reported. Methods: We thus performed a comprehensive pan-cancer analysis and explored the potential oncogenic roles of AJUBA, including gene expression, genetic mutation, protein phosphorylation, clinical diagnostic biomarker, prognosis and AJUBA related immune infiltration based on TCGA and GTEx databases. Results: The results revealed that expression of AJUBA highly correlated with poor clinical outcomes in patients with different types of cancer. Meanwhile, AJUBA expression was positive correlation with cancer-associated fibroblasts (CAFs) in many human cancers, such as breast invasive carcinoma (BRCA), colon adenocarcinoma (COAD), brain lower grade glioma (LGG), lung adenocarcinoma (LUAD), ovarian serous cystadenocarcinoma (OV) and so on. GO and KEGG enrichment analysis showed that AJUBA is mainly involved in protein serine/threonine kinase activity, cell−cell junction, covalent chromatin modification and hippo signaling pathway.